Paediatric multidrug-resistant tuberculosis in a resource-limited high TB burden setting: a case report - Nigam, Samridhi; Sharma, Ravendra K.; Yadav, Rajiv; Rao, V. G.; Bhat, Jyothi (International Journal Of Community Medicine And Public Health, 2022)
MDR-TB is a matter of growing concern especially in children. The case presented here is a four years MDR-TB girl belonging to the Saharia tribe, a high TB burden ethnic group in central India. She was noticed by the project staff during contact tracing visit to the family as her father had MDR TB. The sputum smear and Cartridge- Based Nucleic Acid Amplification Test (CBNAAT) tests confirmed the diagnosis of M. tuberculosis with Rifampicin resistance. She was promptly initiated on shorter MDR regimen under National TB Elimination Programme (NTEP) and was monitored regularly with successful outcome at the end of the treatment. Though household contact investigations are integral part of NTEP, it is rarely done routinely in resource-limited settings, thereby missing a large number of children with TB disease. The carefully performed household contact investigation in this case, led to prompt detection and timely treatment of this MDR-TB girl in the remote setting who was otherwise missed by the routine programme surveillance. This also led to a favorable outcome. The findings emphasize the need for strengthening household contact tracing mechanism in the national TB elimination programme particularly in hard to reach and marginalised ethnic populations in the country.